Investigating Electrical Treeing Initiation in Polyethylene Through Electric Field Modelling with the Finite Element - Mojingkui, Jwellbe Mix; Abd Rahman, Rahisham (Evolution in Electrical and Electronic Engineering, 2024)
This study addresses the critical need to understand the initiation of electrical treeing in polyethylene dielectrics, particularly in cross-linked polyethylene (XLPE), which is widely used in high-voltage insulation systems. Traditional experimental methods for monitoring and predicting electrical treeing are time-consuming, costly, and often lack detailed insight. To overcome these limitations, this research utilizes Finite Element Method (FEM) software to simulate electric field behavior. This approach provides a comprehensive understanding of how high electric field stress, nanofillers, and void defects influence the initiation and progression of electrical treeing in XLPE dielectrics. The Finite Element Method (FEM) enables the prediction of electrical tree behaviour under diverse conditions, which is vital for creating more reliable and long-lasting insulating materials. This research aims to model the geometry and material properties of cross-linked polyethylene (XLPE) in COMSOL, examine various parameters such as voltage stress, and analyze tree development in polyethylene. The methodology involves creating precise geometry, applying relevant physics interfaces, and running simulations to capture electric field distributions and tree growth patterns under varied conditions. Quantitative findings indicate that the likelihood of tree initiation is significantly reduced, approaching 0.3 x 10^7 V/m electric field, when nanoparticles are introduced into the base. This is attributed to the overall electric field becoming less intense compared to raw polyethylene and polyethylene with air voids. This research enhances polyethylene with nanoparticles such as titanium dioxide providing valuable insights for improving electrical insulation system design and reliability.